Performing, Passing, and Covering Motherhood in Academic Spaces: A Heartful Autoethnography (LEARNing Landscapes, 2020)
This study applies heartful autoethnography to demonstrate the performance of being a mother in academia. As such, the article addresses (1) motherhood versus mothering, (2) the concepts of presentation of self, passing, and covering, (3) systematic bias mothers face in academic spaces, and (4) the ultimate costs of covering motherhood in academia.
Keywords: gender in higher education; performance of motherhood; autoethnography; qualitative research; motherscholar; academic mother; Goffman